2015
DOI: 10.1590/s1984-29612015060
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a recombinant protein, A2 family, from Leishmania infantum (Jaboticabal strain) and its evaluation in Canine Visceral Leishmaniasis serological test

Abstract: This study aimed to express a recombinant A2 family protein of Leishmania chagasi, Jaboticabal strain; test this protein as an antigen in serological assays; and investigate its antigenicity and immunogenicity. A protein coded by an allele of the A2 gene isolated from L. chagasi was expressed in three different strains of Escherichia coli. We used 29 sera samples from Leishmune-vaccinated dogs, 482 sera samples from dogs from endemic areas (positive controls), and 170 sera samples from dogs from non-endemic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The DNA positive controls for Leishmania infantum (JUSI et al, 2015), Bartonella henselae (André et al, 2015), Mycoplasma sp. (GONÇALVES et al, 2015), Hepatozoon caimani (BOUER et al, 2017), Babesia vogeli (Jaboticabal strain), Cytauxzoon sp.…”
Section: Fvbp Molecular Screening and Characterizationmentioning
confidence: 99%
“…The DNA positive controls for Leishmania infantum (JUSI et al, 2015), Bartonella henselae (André et al, 2015), Mycoplasma sp. (GONÇALVES et al, 2015), Hepatozoon caimani (BOUER et al, 2017), Babesia vogeli (Jaboticabal strain), Cytauxzoon sp.…”
Section: Fvbp Molecular Screening and Characterizationmentioning
confidence: 99%
“…The expression vector pET 28a containing A2, the target leishmania antigen sequence, was transformed into E. coli BL 21 (DE), ER2566, and Rosetta. As commented by Jusi et al (2015), gene expression of the A2 family mainly occurs at the amastigote stage but not during the promastigote one. Additionally, there is evidence that this antigen is produced in response to stress, thus being important for the survival of Leishmania donavani in visceral organs.…”
Section: E Coli As Host For Leishmania Antigen Expressionmentioning
confidence: 97%
“…In order to develop for a more sensitive and specific recombinant protein-based immunoassay with high capacity for detecting asymptomatic carriers, parasitespecific recombinant antigens such as rK39, rK26, and rA2 have been tested (Porrozi et al 2007;Arruda et al 2016). In this context, Jusi et al (2015) also reported the expression of recombinant A2 family genes of Leishmania chagasi (Jaboticabal strain) that could be useful as a tool for CVL diagnosis using three E. coli BL 21 (DE), ER2566, and Rosetta strains (Table 1). The expression vector pET 28a containing A2, the target leishmania antigen sequence, was transformed into E. coli BL 21 (DE), ER2566, and Rosetta.…”
Section: E Coli As Host For Leishmania Antigen Expressionmentioning
confidence: 99%
“…Nuclear Protein Histone H1 (H1); this antigen induces the protection surface against Leishmania infection (Vakili, Nezafat et al 2022). Protein A2 (A2) plays a major role in parasitic survival in visceral organs of host mammals (Jusi, Oliveira et al 2015). Hydrophilic Acylated Surface Protein B (HASPB), this protein is considered as an immunogen antigen in the host (MacLean, Price et al 2016).…”
Section: Introductionmentioning
confidence: 99%